Linear readout of integrated interferometric biosensors using a periodic wavelength modulation. Issue 2 (5th February 2015) - Dante, Stefania; Duval, Daphné; Fariña, David; González‐Guerrero, Ana Belén; Lechuga, Laura M.
Abstract : To solve the ambiguities affecting interferometric biosensors, a phase modulation system based on variations of the incident wavelength and Fourier deconvolution is presented. The wavelength variation is introduced taking advantage of the power‐wavelength dependence of commercial laser diodes, resulting in a cost‐effective method, valid for all modal interferometers. Considering the modulation of a bimodal waveguide interferometric sensor, limits of detection of 4 · 10 −7 for bulk sensing and 7 ng/ml for the detection of C‐Reactive protein were demonstrated. Abstract: An all‐optical phase modulation method for the linear readout of integrated interferometric biosensors is demonstrated, merging simple intensity detection with the advantages offered by spectral interrogation. The phase modulation is introduced in a simple and cost‐effective way by tuning a few nanometers the emission wavelength of commercial laser diodes, taking advantage of their well‐known drawback of power–wavelength dependence. The method is applied to the case of a bimodal waveguide (BiMW) interferometric biosensor, fabricated with standard silicon technology and operated at visible wavelengths, rendering a detection limit of 4 × 10 − 7 refractive index units for bulk sensing. The biosensing capabilities of the phase‐linearized BiMW device are assessed through the quantitative immunoassay of C‐reactive protein, a key protein in inflammatory processes. This method can be applied to any modal interferometer.